LEGAL BASIS FOR COOPERATION BETWEEN HIGHER EDUCATION INSTITUTIONS AND THE SOCIOECONOMIC ENVIRONMENT - OPPORTUNITIES OR BARRIERS FOR THE DEVELOPMENT OF RELATIONS BETWEEN UNIVERSITIES AND EXTERNAL PARTNERS - Syryt, Aleksandra (Torun International Studies, 2023)
Higher education institutions (HEIs) operate in a specific legal, economic, and social context. Therefore, both areas of their activity, i.e., education and research, must consider the current needs of the socioeconomic environment. In this way, higher education institutions can fulfil their mission: providing top-quality education and scientific activity, shaping civic attitudes, participating in social development, and creating an innovation-based economy. Cooperation between universities and the socioeconomic environment is not a new phenomenon. The formation of the concept of the university confirms that certain political, economic, and social conditions influenced what universities were like. It has not changed, and issues concerning cooperation with external stakeholders are increasingly included in normative acts constituting the higher education system. The article will present basic legal solutions within the sources of generally applicable law concerning the cooperation of higher education institutions with the external partners in Poland and selected countries. At the same time, an attempt will be made to answer the significance of the presented legal solutions for shaping the relations of higher education institutions, especially universities, with external stakeholders. The article is based on a literature review. It focuses on cooperation models as well as opportunities and barriers to developing relations between universities and external partners. The methodology used in the study includes searching relevant databases, applying inclusion and exclusion criteria, extracting and synthesizing data, and analyzing and interpreting the synthesized information. The review includes foreign and Polish literature to ensure a fuller understanding of the national context. The proposed approach has not yet been the subject of detailed analysis in the literature, especially in higher education law.